S100A8/A9 increases the mobilization of pro-inflammatory Ly6Chigh monocytes to the synovium during experimental osteoarthritis - Niels A. J. Cremers; Martijn H. J. van den Bosch; Stephanie van Dalen; Irene Di Ceglie; Giuliana Ascone; Fons van de Loo; Marije Koenders; Peter van der Kraan; Annet Sloetjes; Thomas Vogl; Johannes Roth; Edwin J. W. Geven; et al. (Arthritis Research & Therapy, 2017)
Abstract Background Monocytes are dominant cells present within the inflamed synovium during osteoarthritis (OA). In mice, two functionally distinct monocyte subsets are described: pro-inflammatory Ly6Chigh and patrolling Ly6Clow monocytes. Alarmins S100A8/A9 locally released by the synovium during inflammatory OA for prolonged periods may be dominant proteins involved in stimulating recruitment of Ly6Chigh monocytes from the circulation to the joint. Our objective was to investigate the role of S100A8/A9 in the mobilization of Ly6Chigh and Ly6Clow monocytic populations to the inflamed joint in collagenase-induced OA (CiOA). Method S100A8 was injected intra-articularly to investigate monocyte influx. CiOA was induced by injection of collagenase into knee joints of wild-type C57BL/6 (WT), and S100a9-/- mice. Mice were sacrificed together with age-matched saline-injected control mice (n = 6/group), and expression of monocyte markers, pro-inflammatory cytokines, and chemokines was determined in the synovium using ELISA and RT-qPCR. Cells were isolated from the bone marrow (BM), spleen, blood, and synovium and monocytes were identified using FACS. Results S100A8/A9 was highly expressed during CiOA. Intra-articular injection of S100A8 leads to elevated expression of monocyte markers and the monocyte-attracting chemokines CCL2 and CX3CL1 in the synovium. At day 7 (d7) after CiOA induction in WT mice, numbers of Ly6Chigh, but not Ly6Clow monocytes, were strongly increased (7.6-fold) in the synovium compared to saline-injected controls. This coincided with strong upregulation of CCL2, which preferentially attracts Ly6Chigh monocytes. In contrast, S100a9-/- mice showed a significant increase in Ly6Clow monocytes (twofold) within the synovium at CiOA d7, whereas the number of Ly6Chigh monocytes remained unaffected. In agreement with this finding, the Ly6Clow mobilization marker CX3CL1 was significantly higher within the synovium of S100a9-/- mice. Next, we studied the effect of S100A8/A9 on release of Ly6Chigh monocytes from the BM into the circulation. A 14% decrease in myeloid cells was found in WT BM at CiOA d7. No decrease in myeloid cells in S100a9-/- BM was found, suggesting that S100A8/A9 promotes the release of myeloid populations from the BM. Conclusion Induction of OA locally leads to strongly elevated S100A8/A9 expression and an elevated influx of Ly6Chigh monocytes from the BM to the synovium.